The fondations of the theory of speech acts in pragmatics (Journal of Humanitarian and Applied Sciences, 2020)
This article deals with the most important theory in pragmatics ; That is the theory of speech acts. It introduce it by the factors that led to its emergence, by its dimensions, its pholosophers, how it changed by time?, how it looked at the linguistic sentence? and the language in general?, and what problems it addresses? The most important differences between its founders John Austin and John Searle.
Keywords: Pragmatics; speech acts; Locutionary act; Ilocutionary act; Perlocutionary act